2020
DOI: 10.5539/gjhs.v12n12p27
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Level of Adherence to Laboratory Quality Management System between Public and Private Secondary Health Facilities in Southern Nigeria

Abstract: BACKGROUND: To achieve improved health outcomes of HIV positive patients receiving ART services, quality laboratory services must form an essential part of the services provided. The aim of this study was to compare service quality by assessing the level of adherence to quality system essentials (QSEs) in laboratory services delivered by public and private health institutions in Southern Nigeria. METHODS: This was an analytical cross-sectional study conducted among 50 health facilities’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Compromise in quality control issues has an impact on the credibility of the results produced by the laboratory and the CoLTeP program reaffirmed the importance of quality control. On the contrary, a study in Nigeria observed that quality control and quality assurance was more in private sector as compared to the public health sector [ 17 ]. Furthermore, lack of biosafety training for laboratory staff was identified as one of the major non conformities across the audited laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Compromise in quality control issues has an impact on the credibility of the results produced by the laboratory and the CoLTeP program reaffirmed the importance of quality control. On the contrary, a study in Nigeria observed that quality control and quality assurance was more in private sector as compared to the public health sector [ 17 ]. Furthermore, lack of biosafety training for laboratory staff was identified as one of the major non conformities across the audited laboratories.…”
Section: Discussionmentioning
confidence: 99%